SOFTWARE REUSING AND ITS IMPACT ON THE SYSTEM'S COST - Lorena Lazo, Paul (2004)
This article presents two programs in C# that use an SQL server 2002 data access component, which is modified to be used with a 9i data base, with the purpose of evaluating a developer's productivity, making the comparative analysis of two stages: a system developed reusing software, and another one without software reusing.